The Juridical Analysis of Role & Responsibility of Notaries in Dispute Settlement with Mediation - Zamaludin Zamaludin; Jawade Hafidz (Sultan Agung Notary Law Review, 2021)
This journal will explore and discuss in order to be able to analyze and be able to find out about Juridical Analysis of the Role and Responsibilities of Notaries in Settlement of Disputes by Mediation/Peace. In this case Problem A peace deed is an agreement between two or more parties in which they request legal force assisted by a mediator in accepting and carrying out the contents of the agreed agreement. Peace decisions have executive power as described in Article 1858 of the Civil Code (hereinafter referred to as the Civil Code), Article 130 HIR paragraphs 2 and 3. Based on this, the peace agreement resulting from a dispute resolution process must be stated in written form, it aims to prevent the re-emergence of the same dispute in the future. This legal research aims to find out what is the role of a notary in settlement with peace outside the court and how is the responsibility of a notary in resolving disputes against a peace deed made before a notary and what is the legal force of a peace deed made before a notary. In this case deed of peace can be in the form of an underhand deed or an authentic deed made by a notary. This research is a normative juridical research that is used is the approach, namely: the juridical approach is used for research that refers to existing literature studies or to the secondary data used. While the normative approach is used to obtain normative knowledge about the relationship between one regulation and another and its application in practice. Types of legal materials used: Primary Legal Materials, Secondary Legal Materials and Tertiary Legal Materials obtained through literature study and data obtained from related parties. That is in Juridical Analysis of the Roles and Responsibilities of Notaries in Settlement of Disputes Amicably